2020
DOI: 10.7567/1347-4065/ab6341
|View full text |Cite
|
Sign up to set email alerts
|

Development of carbon nanotube organic thermoelectric materials using cyclodextrin polymer: control of semiconductor characteristics by the solvent effect

Abstract: The π-type organic thermoelectric conversion modules composed of p-type and n-type materials that convert low-temperature waste heat into electric energy have the potential to significantly increase energy efficiency. However, p-type and n-type materials are difficult to prepare by similar methods since they have opposite carriers. In this study, we achieved γ-cyclodextrin polymer-carbon nanotube (PγCyD-CNT) composite thermoelectric film that can control the carrier by the solvent effect. When the preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Although some research groups have created n-type CNT materials stable in air near room temperature, the stability at elevated temperature has not been tested adequately. Several reported Seebeck measurements of n-doped CNTs at elevated temperatures were conducted under inert He gas atmosphere instead of air 23 , 53 . To the best of our knowledge, only the study by Nonoguchi and Kawai et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some research groups have created n-type CNT materials stable in air near room temperature, the stability at elevated temperature has not been tested adequately. Several reported Seebeck measurements of n-doped CNTs at elevated temperatures were conducted under inert He gas atmosphere instead of air 23 , 53 . To the best of our knowledge, only the study by Nonoguchi and Kawai et al .…”
Section: Resultsmentioning
confidence: 99%
“…p-Type doping of CNTs is rather easy because the CNTs readily accept holes from naturally adsorbed oxygen molecules in air 22 . In contrast, CNTs after n-type doping tend to lack air stability due to dopant volatilization 23 and/or autoxidation of the electron-injected CNTs by oxygen in air. For example, alkali metal deposition on the CNT surface produces metal cation and available electron to promote a heavily n-doped state 24 ; however, this n-type polarity could not be retained upon exposure to air.…”
Section: Introductionmentioning
confidence: 99%
“…359−366 Over the past decade, TE composites with CNT conductive fillers have regularly achieved room-temperature TE power factors exceeding 100 μW m −1 K −2 . [339][340][341][342][343][344][345][346][347][348][349][350][351][352][353][354][355]357,358,[361][362][363][364]366 For a thorough review of polymer-based blended TE composites with carbon nanotube fillers, we direct the reader to recent reviews by Blackburn et al 208 and Nandihalli et al 367 Here we will focus on key advances in blended TE composites comprising organic host matrices and CNT inclusions.…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
“…More recently, Hata et al demonstrated composites of CNTs embedded in a γcyclodextrin polymer cross-linked with epichlorohydrin (PγCyD) that exhibit TE power factors >200 μW m −1 K −2 for both p-type and n-type transport (Figure 40). 354 The difference in the majority carrier type was attributed to different interactions between the processing solvent, either H 2 O or Nmethyl-2-pyrrolidone (NMP), where the "pocket" in the γCyD macrocycle is capable of hosting the NMP molecule (Figure 40b), leading to enhanced n-type behavior than for an equivalent composite prepared from polyvinylpyrrolidone (PVP).…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation